Role of cold rolled followed by annealing on improvement of hydrogen induced cracking resistance in pipeline steel. (September 2018) - Mohtadi-Bonab, M.A.; Eskandari, M.; Szpunar, J.A.
Abstract: In this study, we investigated the effect of cold rolled followed by annealing on hydrogen induced cracking susceptibility in an API X60 pipeline steel. To this, we carried out cold rolling on X60 steel up to 20%, 50% and 90% in thickness reduction to change the microstructure and texture of steel. Then, we annealed all specimens at 850 °C for 90 s. We studied all tested specimens by electron backscatter and X-ray diffraction techniques. EBSD results showed that the grain refinement process was properly done via cold rolling and annealing treatments in tested specimens. However, the dislocation density was high for all tested steels. Moreover, electrochemical hydrogen charging experiment on tested steels proved that all specimens were still highly susceptible to hydrogen induced cracking. Therefore, we increased the annealing temperature and its duration of the 90% cold rolled specimen (the specimen with finest grains) up to 950 °C for 5 min. Interestingly, there was no HIC crack on this steel after hydrogen charging experiment. EBSD measurements on this steel showed strong textures of 100//ND and 111//ND. As a result, such strong textures, low Kernel Average Misorientation data, a high proportion of recovered grains and coincidence site lattice boundaries were recognized as the most important reasons for the highest HIC resistance in the mentioned steel. Highlights: We investigated effect of thermomechanical control processing on HIC susceptibility in pipeline steel. Grain refinement was obtained through cold-rolling and annealing treatments. Strong crystallographic texture in pipeline steels has a beneficial effect on improving HIC resistance. Fine equiaxed grains with a minimum stored energy increase HIC resistance in pipeline steels. Coincidence site lattice boundaries may provide a resistant path for intergranular HIC crack propagation.